HIV Infection Among Adolescent Girls and Young Women in Sub-Saharan Africa: Philosophical Perspectives of Sociostructural Risk Factors - Matovu, Iddi; Musoke, Miph; Ddamulira, Christopher (International Journal of Translational Medical Research and Public Health, 2024)
Background and Objective: Sociostructural risk factors influence human immunodeficiency virus (HIV) infection outcomes among adolescent girls and young women (AGYW) aged 15–24 in Sub-Saharan Africa. The philosophical perspectives on sociostructural risk factors can be helpful in reducing new HIV infections in this age group. This review aims to describe these perspectives to guide the development and implementation of targeted interventions at preventing new HIV infection among AGYW, while addressing age-gender inequalities in HIV infection risk reduction. Methods: This literature review examined philosophical perspectives on sociostructural risk factors of HIV infection from June 1981 when improvements in HIV knowledge regarding clinical course and epidemiology began to November 2023. We utilized literature from peer-reviewed papers and books on HIV risk factors and infection outcomes among AGYW, gathered from search engines like PubMed, Google Scholar, and Medline. Results: The philosophy of sexuality is linked to sociostructural tenets like seduction, early marriage, adultery, and prostitution. Ubuntu’s philosophy is influenced by Western culture, such as pornography and adolescent marriages. Realism is linked to sexual violence, HIV stigma, and unfavorable health policy decisions. The philosophy of health integrates natural and holistic phenomena to address HIV infection. Conclusion and Implications for Translation: The literature reviews suggest that addressing philosophical issues like seduction, early marriages, adultery, prostitution, pornography exposure, sexual violence, and unfavorable policies are crucial for reducing new HIV infection among AGYW and recommend the Ministries of Health to review and adopt these considerations in their respective national HIV prevention guidelines. Keywords: Philosophical Overview, Sociostructural Determinants of Health, HIV, Risk, Adolescent Girls, Young Women